The Premise and Promise of Indigenous Archaeology. Issue 2 (20th April 2010) - Colwell-Chanthaphonh, Chip; Ferguson, T. J.; Lippert, Dorothy; McGuire, Randall H.; Nicholas, George P.; Watkins, Joe E.; Zimmerman, Larry J.
Abstract : Researchers have increasingly promoted an emerging paradigm of Indigenous archaeology, which includes an array of practices conducted by, for, and with Indigenous communities to challenge the discipline's intellectual breadth and political economy. McGhee (2008) argues that Indigenous archaeology is not viable because it depends upon the essentialist concept of "Aboriginalism." In this reply, we correct McGhee's description of Indigenous Archaeology and demonstrate why Indigenous rights are not founded on essentialist imaginings. Rather, the legacies of colonialism, sociopolitical context of scientific inquiry, and insights of traditional knowledge provide a strong foundation for collaborative and community-based archaeology projects that include Indigenous peoples.